2015
DOI: 10.1371/journal.pone.0140963
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Bioavailability from Glucoraphanin-Rich Broccoli: Control by Active Endogenous Myrosinase

Abstract: Glucoraphanin from broccoli and its sprouts and seeds is a water soluble and relatively inert precursor of sulforaphane, the reactive isothiocyanate that potently inhibits neoplastic cellular processes and prevents a number of disease states. Sulforaphane is difficult to deliver in an enriched and stable form for purposes of direct human consumption. We have focused upon evaluating the bioavailability of sulforaphane, either by direct administration of glucoraphanin (a glucosinolate, or β-thioglucoside-N-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 30 publications
(69 reference statements)
11
124
0
1
Order By: Relevance
“…We did quality control testing of gel capsules stored at each of the three clinical centers over the course of the study that demonstrated that the sulforaphane content of the gel capsules was stable. Furthermore, sulforaphane has been shown to be bioavailable from gel caps and, similar to juice preparations, to be metabolized rapidly [20,2729]. We confirmed that sulforaphane was well absorbed as evident from the levels of its dithiocarbamate metabolites in the plasma of participants.…”
Section: Discussionsupporting
confidence: 73%
“…We did quality control testing of gel capsules stored at each of the three clinical centers over the course of the study that demonstrated that the sulforaphane content of the gel capsules was stable. Furthermore, sulforaphane has been shown to be bioavailable from gel caps and, similar to juice preparations, to be metabolized rapidly [20,2729]. We confirmed that sulforaphane was well absorbed as evident from the levels of its dithiocarbamate metabolites in the plasma of participants.…”
Section: Discussionsupporting
confidence: 73%
“…The extract was standardized to 100 µmol sulforaphane in the form of 2 gel capsules per day over 7 consecutive days, as described previously [45, 53-58]. The dose of 100 μmol sulforaphane and the 7-day treatment duration were determined empirically from previous studies, including a trial demonstrating induction of antioxidant enzymes in nasal lavage cells of human subjects [59] and improved excretion of air pollutants [56].…”
Section: Methodsmentioning
confidence: 99%
“…The dose of 100 μmol sulforaphane and the 7-day treatment duration were determined empirically from previous studies, including a trial demonstrating induction of antioxidant enzymes in nasal lavage cells of human subjects [59] and improved excretion of air pollutants [56]. Our formulation of sulforaphane is 80% bioavailable [58], reaches peak plasma levels 1 h after oral ingestion, declines with first-order kinetics, and is actively excreted in urine (60% at 8 h) [58, 60]. …”
Section: Methodsmentioning
confidence: 99%
“…This compound is a member of the isothiocyanate family and obtained from cruciferous vegetables including Brussels sprouts, cabbage, and broccoli [62]. Sawai et al evaluated the effect of SFN and radiation treatment on LM8 murine OS cells.…”
Section: Chemopreventive Agents and Anti-cancer Compoundsmentioning
confidence: 99%